A Unification of Intuitionistic Fuzzy Calculus Theories Based on Subtraction Derivatives and Division Derivatives - Lei, Qian; Xu, Zeshui (IEEE transactions on fuzzy systems, 2017)
Intuitionistic fuzzy calculus replaces real numbers in classical calculus with intuitionistic fuzzy numbers that are the basic elements of Atanassov's intuitionistic fuzzy sets. Intuitionistic fuzzy calculus consists of two parallel parts, which are respectively developed based on the subtraction derivatives and the division derivatives. This paper focuses on building the relationships between the two independent intuitionistic fuzzy calculus theories, and unifying them into a whole theory.